The third international meeting on genetic disorders in the RAS/MAPK pathway: Towards a therapeutic approach. (21st April 2015) - Korf, Bruce; Ahmadian, Reza; Allanson, Judith; Aoki, Yoko; Bakker, Annette; Wright, Emma Burkitt; Denger, Brian; Elgersma, Ype; Gelb, Bruce D.; Gripp, Karen W.; Kerr, Bronwyn; Kontaridis, Maria; et al.
<x xml:space="preserve">Abstract</x> "The Third International Meeting on Genetic Disorders in the RAS/MAPK Pathway: Towards a Therapeutic Approach" was held at the Renaissance Orlando at SeaWorld Hotel (August 2–4, 2013). Seventy‐one physicians and scientists attended the meeting, and parallel meetings were held by patient advocacy groups (CFC International, Costello Syndrome Family Network, NF Network and Noonan Syndrome Foundation). Parent and patient advocates opened the meeting with a panel discussion to set the stage regarding their hopes and expectations for therapeutic advances. In keeping with the theme on therapeutic development, the sessions followed a progression from description of the phenotype and definition of therapeutic endpoints, to definition of genomic changes, to identification of therapeutic targets in the RAS/MAPK pathway, to preclinical drug development and testing, to clinical trials. These proceedings will review the major points of discussion. © 2015 Wiley Periodicals, Inc.